2009
DOI: 10.1038/gt.2009.23
|View full text |Cite
|
Sign up to set email alerts
|

AAV for pain: steps towards clinical translation

Abstract: Recombinant adeno-associated virus (rAAV) vectors consisting of self-complementary genomes and packaged in certain capsids can target primary sensory neurons efficiently and can control neuropathic pain long term by expressing opioid or non-opioid analgesic genes. This review examines the therapeutic potential of the approach in five sections: Pain control in oncology (including a discussion of cancer centers as translational pain research environment); vector biology; safety considerations and immunological l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 58 publications
0
30
0
Order By: Relevance
“…In addition, DRG transduction could have potential benefit in models of chronic pain (Federici and Boulis, 2007;Storek et al, 2008;Beutler and Reinhardt, 2009). Xu et al have achieved strong GFP expression with AAV vector in DRG, dorsal roots, and peripheral axons (Xu et al, 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, DRG transduction could have potential benefit in models of chronic pain (Federici and Boulis, 2007;Storek et al, 2008;Beutler and Reinhardt, 2009). Xu et al have achieved strong GFP expression with AAV vector in DRG, dorsal roots, and peripheral axons (Xu et al, 2003a).…”
Section: Discussionmentioning
confidence: 99%
“…For example, recombinant adeno-associated virus (rAAV) was used as mediators for delivery miRNA134 in mice resulting in almost 100% transduction efficiency (Christensen et al, 2010). rAAV can target non-dividing cells and show transgene expression in a long term with relatively non-pathogenic and considered safe nature (Beutler and Reinhardt, 2009). Clinical trials of rAAV gene therapy in PD also showed that they were well tolerated in the human CNS and expressed persistence of transgenes in a long-term (Kaplitt et al, 2007; Marks et al, 2008).…”
Section: Vector Systems To Deliver Mirnasmentioning
confidence: 99%
“…Furthermore these data act as an independent proof of principle that inhibiting GCH1 in patients may well be an effective anti-neuropathic. It remains to be seen if this particular delivery system will be effective in humans, but if clinical trials for other conditions are successful [164, 165] chronic neuropathic pain would certainly be a first line target for such viral constructs [166]. …”
Section: Other Evidence Of Gch1 Link To Painmentioning
confidence: 99%